Predictability of Work Demands and Professionalization as Determinants of Workers' Discretion - Bell, Gerald D. (Academy of Management Journal, 1966)
Assume that you have been asked by the president of a large firm to advise him on the most desirable levels of decentralization in order to control the activities of different departments within his organization. Upon what factors would you be likely to base your decision? A recent investigation indicates that to establish appropriate levels of decentralization, one's decisions should be, at least partially, based on: the types of productive tasks workers perform in general; and, the degree of predictability of work demands, in particular.1 This paper provides a partial explanation of several non-administrative cause for differences in the degrees of discretion workers exert in performing their tasks. Specifically we attempt to trace the influence of two factors upon discretion. One is the predictability of work demands; the other is the professionalization of jobs. Before attempting to analyze these relationships, let us take a brief view of the research design and the components of discretion.